2019
DOI: 10.1101/752170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal scaling in developmental gene networks by epigenetic timing control

Abstract: During development, progenitors follow defined temporal schedules for differentiation, to form organs and body plans with precise sizes and proportions. Across diverse contexts, these developmental schedules are encoded by autonomous timekeeping mechanisms in single cells.These autonomous timers not only operate robustly over many cell generations, but can also operate at different speeds in different species, enabling proportional scaling of temporal schedules and population sizes. By combining mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 134 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…The methylation-compaction switching mechanism could underlie diverse cell-autonomous timers that have been observed to work independently of cell division ( Burton et al, 1999 ; Gao et al, 1997 ; Heinzel et al, 2017 ; Li et al, 2019 ; Okamoto et al, 2016 ; Osmond, 1991 ; Otani et al, 2016 ). Measuring elapsed time independently of cell division could enable unique functions, including operation in non-dividing cells and constancy amid changes to cell proliferation, which could allow for tunable population size control, an idea we explore in a separate study ( Nguyen et al, 2019 ). Our simulations revealed that such division-independent timing control requires active turnover of H3K27me3 and nucleosome compaction dynamics to be rapid compared to the cell cycle length ( Methods S1 ; Figure S5F ).…”
Section: Discussionmentioning
confidence: 99%
“…The methylation-compaction switching mechanism could underlie diverse cell-autonomous timers that have been observed to work independently of cell division ( Burton et al, 1999 ; Gao et al, 1997 ; Heinzel et al, 2017 ; Li et al, 2019 ; Okamoto et al, 2016 ; Osmond, 1991 ; Otani et al, 2016 ). Measuring elapsed time independently of cell division could enable unique functions, including operation in non-dividing cells and constancy amid changes to cell proliferation, which could allow for tunable population size control, an idea we explore in a separate study ( Nguyen et al, 2019 ). Our simulations revealed that such division-independent timing control requires active turnover of H3K27me3 and nucleosome compaction dynamics to be rapid compared to the cell cycle length ( Methods S1 ; Figure S5F ).…”
Section: Discussionmentioning
confidence: 99%